1996
DOI: 10.1007/bf02174026
|View full text |Cite
|
Sign up to set email alerts
|

Structural genes for Mg-chelatase subunits in barley:Xantha-f, -g and-h

Abstract: Barley mutants in the loci Xantha-f, Xantha-g and Xantha-h, when fed with 5-aminolevulinate in the dark, accumulate protoporphyrin IX. Mutant alleles at these loci that are completely blocked in protochlorophyllide synthesis are also blocked in development of prolamellar bodies in etioplasts. In contrast to wild type, the xan-f, -g and -h mutants had no detectable Mg-chelatase activity, whereas they all had methyltransferase activity for synthesis of Mg-protoporphyrin monomethyl ester. Antibodies recognising t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 26 publications
6
65
1
Order By: Relevance
“…If porphyrin substrate is limiting, the difference in K m values is more than sufficient to account for the higher flux into the Mg 2ϩ branch of the pathway. Regulation of the branch point by relative affinity for the substrate could work in addition to a mechanism of day versus night regulation, based on the demonstrated circadian rhythmicity of subunit H expression (Gibson et al, 1996;Jensen et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If porphyrin substrate is limiting, the difference in K m values is more than sufficient to account for the higher flux into the Mg 2ϩ branch of the pathway. Regulation of the branch point by relative affinity for the substrate could work in addition to a mechanism of day versus night regulation, based on the demonstrated circadian rhythmicity of subunit H expression (Gibson et al, 1996;Jensen et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…The same is true for the two plant genes that have been identified (Hudson et al, 1993;Nakayama et al, 1995;Gibson et al, 1996;Jensen et al, 1996b). Although most of our work on the in vitro characterization of the Mg-chelatase reaction has used membrane-containing chloroplast fractions, we have observed that Mg-chelatase activity can be solubilized by chloroplast lysis in buffers that contain low concentrations of MgCl 2 (Walker and Weinstein, 1995).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…To do this, we targeted both a nuclear transgene encoding luciferase (luc) and an endogenous gene coding for an enzyme required in chlorophyll biosynthesis. Magnesium chelatase is a multi-subunit protein that catalyzes the insertion of magnesium into protoporphyrin IX (Jensen et al, 1996). In tobacco, a mutated allele (Su) of one subunit causes the phenotype known as 'sulfur' (Nguyen, 1995).…”
Section: Introductionmentioning
confidence: 99%